PRINCIPLES OF TERMINATION CONTROL OF UNMANNED AERIAL VEHICLES FLIGHT PATH - Kondrashov, Ya.V.; Arutyunyan, A.K.; Kravchyshyn, I.O. (Science-based technologies, 2009)
For realization of control of gliding aircraft descend from  the  flight path  to  the defined area of  the space  let’s propose its non autonomous control principle. The method of control is shown, a goal, tasks and command con-trol program are defined.